Subjectivity and Pragmatic Strategies in Elderly Rights-Protection Discourse - Peng, Bingzhuan; Sun, Xiaodan (Studies in Social Science & Humanities, 2025)
Taking elderly rights-protection discourse on online platforms, this study examines its subjectivity and pragmatic strategies from the perspectives of pragmatics and discourse analysis. The findings reveal that the connotations of the subjectivity in elderly rights-protection discourse are mainly manifested in emotional appeals, attitude expressions and cognitive judgments. These are presented and encoded through pragmatic strategies at lexical, syntactic, and textual levels, including lexical strategies such as negative vocabulary, concrete vocabulary, and vague vocabulary, syntactic strategies such as mood and discourse markers, and textual strategies like hardship narratives. The research uncovers the underlying subjective tendency and pragmatic patterns in elderly rights discourse, providing valuable references for the studies of aging discourse and discourse analysis and contributing to a deeper pragmatic understanding of the subjectivity embedded in elderly rights protection discourse.